THE EFFECT OF LEADERSHIP STYLE, EMPLOYEE EFFECTIVENESS, SUPERVISOR SUPPORT ON EMPLOYEE PRODUCTIVITY, EMPLOYEE SATISFACTION DIMENSION AT PT. JAYA CONSTRUCTIO - Nafa Ira Riyandini; Mohamad Trio Febriyantoro (Research Trend in Technology and Management, 2023)
The problem in this study is whether the Transformational Leadership Style and Job Satisfaction have a positive and significant influence and which variable has the dominant influence on Employee Productivity at Pt. Jaya contruction. To answer these problems, descriptive analysis methods are used, quantitative analysis with multiple regression analysis tools. From the results of the statistical test analysis, it shows that the Transformational Leadership Style has a positive and significant effect on Nurse Performance while job satisfaction has no effect and is not significant on Nurse performance at Pt. Jaya construction. The first hypothesis proposed is proven while the second hypothesis is not proven. From the results of the regression coefficient, it can be seen that the variable that has a more dominant effect on employee performance is the Influence of Transformational Leadership Style, namely that the third hypothesis proposed is proven. The results of regression testing show that the variable Transformational Leadership Style has a positive and significant effect on Nurse employee productivity while the variable Job Satisfaction does not have a positive and significant effect on Nurse Performance, while the dominant variable that influences Nurse Performance is Transformational Leadership Style